An analysis of factors affecting the performance of disaster management agency - Susi Handayani (Proceedings of AICS - Social Sciences, 2017)
The purpose of Disaster Management Agency is to help the victims of disasters that often occur in our country. This research uses descriptive approach, by focusing on problems and phenomena that existed at the time of the research. Researchers multiply data and information from several disaster occurrence sites and distributing questionnaires to obtain more accurate data. The results of the research show there are several factors that cannot be met by the Disaster Management Agency. These factors make the performance of Disaster Management Agency to be not optimal and cause dissatisfaction for the victims of disaster. The conclusion is the lack of coordination between levels in the Disaster Management Agency, poor communication between the field (technical) with the part or higher level and the motivation of members who are still relatively low and the weakness of existing human resource capacity. Some things that should be done by the Disaster Management Agency, such as the improvement of internal facilities, improve the communication system and pay attention to the needs of its members.